Biosynthetic classification of flavanoids (vitamins P) - Levitsky, A.; Selivanskaya, I. (Journal of Education, Health and Sport, 2026)
Annotation The vast number of compounds based on the three-membered flavan ring and possessing vitamin P activity requires a specific systematization of flavanoids. Existing classifications, unfortunately, do not take into account the full diversity of these compounds, including their biogenesis. We have proposed a classification of flavonoids with P-vitamin activity that takes into account their biosynthesis and interconversions. This so-called biosynthetic classification divides all flavonoids into 11 classes: 1 – chalcones, 2 – flavanones, 3 – flavanols, 4 – flavones, 5 – isoflavones, 6 – dihydroflavanol, 7 – flavon-3-ols, 8 – flavandiols (leucoanthocyanidins), 9 – anthocyanidins, 10 – flavan-lignans, 11 – atypical and modified flavanoids.